Does relationship matter? The choice of financial advisors - Bill B. Francis; Iftekhar Hasan; Xian Sun (Bank of Finland, 2012)
Using a sample of U.S. mergers and acquisitions, this study evaluates how banking relationships influence acquirers choice of financial advisors. Specifically, it examines: i) acquirers previous relationships with advisors in various financial activities: M&A advisories, equity issuings and lending activities; ii) the optimism of analyst recommendations; and iii) how acquirers past satisfaction with their financial advisors determines the choice of financial advisors. Overall, the findings suggest that the influence of banking relationships on a firm s choice of financial institutions is limited in the area of M&A advisory business. The implications from the traditional relationship banking studies may not be suitable to explain how firms choose advisors, due to the wide variety of practices in investment banking activities. The evidence portrays that firms with M&A experience are more likely to switch financial advisors with poor deal outcomes. Firms without M&A experience, on the other hand, are more likely to choose their underwriters as financial advisors, especially when they provide overly optimistic analyst coverage prior to the transactions.
URN:NBN:fi:bof-20140807235
Keywords: 330